Improvement in corrosion resistance of AZ91D Mg alloy in simulated body fluid by cerium-based/stearic acid composite coatings - Loperena, Ana Paula (2024)
Magnesium alloys have attracted attention due to their biocompatibility and biodegradability.In this work, composite coatings are developed to potentially improve the corrosion resistanceof AZ91D Mg alloy in simulated physiological fluid. Cerium-based/stearic acid coatings wereprepared by electrodeposition combined with a simple immersion method. The effect of stearicacid bath concentration on the contact angle and corrosion resistance of the composite coatingswas evaluated. The results showed that the stearic acid treatment increased the hydrophobicityof the surfaces of the cerium-based simple coatings. The use of an appropriate stearic acidconcentration is a key for the fabrication of hydrophobic surfaces. The duplex coatings weredemonstrated to protect the substrate from corrosion in Ringer solution.